Investor Attention from Google Trends and CPI Inflation Rate in the Philippines - Janna Paro Janna Paro; Alyssa Ashley G. Odchigue; Karl P. Campos (Universitas YARSI, 2025)
This quantitative research study examined whether investor attention can empirically explain and forecast Consumer Price Index (CPI) inflation in the Philippines. Thus, it addresses gaps in previous research by examining whether investor attention, as measured by Google Trends, influences and potentially forecasts inflation in the Philippines' Consumer Price Index (CPI) inflation rate. Using Granger causality tests and the Vector Autoregression (VAR) model on monthly data from 2004 to 2025, the study reveals that inflation persistence is the leading cause of current inflation rates. The results show that fluctuations in the oil price have a significant but temporary effect on inflation in the Philippines, which is primarily caused by its persistence. In comparison, investor attention shows only delayed and inconsistent effects on inflation, lacking robust predictive capability. This shows how investor attention affects inflation by influencing inflation expectations. However, the empirical results rejected every hypothesis in this study: investor attention neither significantly explains nor reliably forecasts inflation, nor does it systematically influence inflation via expectations.